Isolation, purification and identification of the alkaloid of the seeds of Anona muricata Linn. - Pham-Minch-Chau 1938-
The present study consists in the isolation and identification of an alkaloid from the seeds of Anona muricata Linn. (Guayabano, Tag.). The phenolic base was crystallized as the picrate, C18H1903N. C6H3N3O7. It melts at 210 (degrees C) with decomposition. Analysis of the U.V., I.R., and mass spectra as well as the chemical and physical characteristics of the picrate clearly show that it is a benzylisoquinoline alkaloid.
Available to the general public.
Thesis (Master of Science in Chemistry)--University of the Philippines, April 1971.
Keywords: Alkaloids; Guayabano